2020
DOI: 10.3341/kjo.2019.0108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Delayed-onset Consecutive Esotropia after Surgical Correction of Intermittent Exotropia

Abstract: Consecutive esotropia (ET) is a persisting or variable esodeviation after surgery to correct exotropia. The prevalence of such surgical overcorrection in patients with exodeviation ranges from 6% to 20% [1,2]. Risk factors for consecutive ET include lateral incomitancy [3], high ac-Purpose: To evaluate the clinical features and prognosis of a delayed-onset consecutive esotropia (ET) after surgical correction of intermittent exotropia. Methods: Thirty-four patients who developed consecutive ET after primary bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, high AC/A ratios or lateral rectus underaction and/or stronger MR tension following release of tension from recession of the lateral recti could be associated with this phenomenon. Baik et al [22] recently asserted that the cause of delayed-onset consecutive esotropia is unknown, but an increase in "near work" in the current generation during the unstable postoperative period within several early months after surgery may be playing a role. In addition, as children undergo emmetropisation or myopic shift, changes in the refractive error should be considered during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high AC/A ratios or lateral rectus underaction and/or stronger MR tension following release of tension from recession of the lateral recti could be associated with this phenomenon. Baik et al [22] recently asserted that the cause of delayed-onset consecutive esotropia is unknown, but an increase in "near work" in the current generation during the unstable postoperative period within several early months after surgery may be playing a role. In addition, as children undergo emmetropisation or myopic shift, changes in the refractive error should be considered during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…However, to maintain eye position, the non-fixing eye may use convergence. This will lead to a difference in binocular accommodation, resulting in bilateral eye competition, which will cause a decrease in AF and accommodative response ( 12 ). This is consistent with the results of this study, in which it was found that the AMP of non-fixing eyes in patients with IXT is higher than that of their fixing eyes, suggesting that their fixing eyes should exhibit clear vision in everyday use.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Choi [115] reported that the divergence-excess type X (T), amblyopia, BLR, esodeviation ≥ 20 PD at postoperative day 1, younger age at diagnosis and surgery, and shorter duration from onset to surgery Surgical Treatment of Intermittent Exotropia were risk factors for consecutive esotropia. Baik et al [112] found that 79% of consecutive esotropia were patients who underwent BLR that were orthotropic after 1 month, then later developed esodeviation within 7.4 ± 6.0 months (range, 2 to 29 months). Lee and Kim [113] also found that 5% (13/284) of the patients developed consecutive esotropia after showing orthotropia or exodeviation at postoperative 1 month.…”
Section: Xiii-2 Management Of Consecutive Esotropiamentioning
confidence: 99%
“…Residual exotropia at postoperative 1 week and 1 month led to recurrence [ 25 , 26 , 104 ]. However, few patients may manifest delayed consecutive esotropia after showing orthotropia to exotropia at postoperative 1 month, especially after BLR [ 112 , 113 ]. Therefore, surgeons should recognize the possibility of delayed development of consecutive esotropia.…”
Section: Factors Affecting Surgical Outcomesmentioning
confidence: 99%